KARTU KUARTET BOELANG (BOEDAYA LAMPUNG) SEBAGAI MEDIA EDUKASI BOEDAYA LOKAL DI SMPN BANDARLAMPUNG - Sumargono Sumargono; Lisnawati Lisnawati; Siti Rohmayani; Masdi Masdi (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
The aim of the research is developing of learning media of art and culture that suitable with teachers and students needs for learning activities in the class. This research try to develop the Boelang (Boedaya Lampung) Quartet card as a media for local culture education at SMPN (Public Junior High School) in Bandar Lampung. Research & Development (R & D) method used as the research method for this research which refers to Thiagarajan model. Sources of data are collected by interviews, tests, observations, and documentation. Test of product effectiveness is carried out by the experimental method. This research conducted in SMPN 22Bandar Lampung. Class VIII H as an experimental group, and class VIII F as the control group. Based on the effectiveness test analysis, the results of the experimental post-test (using developed media) results of the SPSS 16 analysis showed significant at 0,000 <0,05, which means there are significant result between the experimental class and the control class after treated. Because the average test score of the experimental class (the group using the Boelang Quartet Card) = 84,15 > with the average test score of control class (the group using power point) = 74,91 so it can be concluded that the Boelang Quartet Card is more effective as a local culture education media for students.